Tinjauan Polemik Identitas dan Karakteristik Tafsir Tarjuman al-Mustafid Karya Abd al-Rauf al-Singkili - Billah Ali, Asyiq; Faruqi, Amir (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
This study examines the polemics over the identity and characteristics of Abd al-Rauf al-Singkili's Nusantara tafsir book, Tafsi>r Tarjuma>n al-Mustafi>d. Which many consider that this tafsir book is a duplication and translation of previously existing tafsir books, such as Tafsir Jalālayn, Tafsir al-Khāzin, and Tafsir al-Baydawi. This research is explored through a qualitative method with a Library Research approach. Because the sources used are primary literature in the form of Tafsi>r Tarjuma>n al-Mustafi>d and supported by secondary literature from books, journal articles, and so on. The results of this study found evidence that the book of Tafsi>r Tarjuma>n al-Mustafi>d is an original book of interpretation and adaptive application. And the assumptions and accusations of orientalists against Tafsi>r Tarjuma>n al-Mustafi>d are unfounded.